PERANAN PENYULUH PERTANIAN DALAM PENGUATAN USAHATANI BAWANG DAUN DI KECAMATAN SUKAPURA KABUPATEN PROBOLINGGO - Darmaludin Darmaludin; S. Suwasono; R E. Muljawan (Universitas Tribhuwana Tunggadewi, 2012)
This study aims to determine the role of agricultural extension relationship as (motivator, dynamist, facilitator) to the success of farmers in farming scallion and a general farm (costs, revenues and profits) scallion, in district Sukapura Probolinggo. Analysis of the data used include: (a) the role of agricultural extension relationship as (motivator, dynamist, facilitator) to the success of farmers in farming scallion with spearman rank test (b) know the description of the analysis used scallion farm profits, revenues, R/C ratio, results showed that each independent variable role of agricultural extension as (motivator, dynamist, facilitator) has a real connection to the strengthening of scallion farms in the village of Ngadisari, Ngadirejo. The results of spearman rank test showed that the role of agricultural extension that gives the highest correlation to the success of the farmers is the facilitator (t test 0.762) and the probability of sig ≤ 0.05. Facility is an important factor to consider in relation to the success of the farmers. A good facility is able to generate a positive image of farmers, so that will affect farmers in the farming village Ngadisari scallion, Ngadirejo. Scallion farms in the district Sukapura profitable with an average profit of Rp 7,782,451.22/ha. Value of R/C ratio for the land, amounting to 1.623. This means the scallion farms in the district Sukapura was worth at try